Visualization of Learning and Memorizing Processes Using Mobile Devices: Mind Mapping and Charting - Vorona-Slivinskaya, Lubov; Bokov, Dmitry; Li, Olga (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The purpose of the study is to test the effectiveness of visualization of learning and memorization in the educational process in higher educational institutions. The research was carried out in higher educational institution in the Russian Federation among 1-4-year students as well as teachers. The sample included 200 students and 35 teachers. The experiment consisted of three stages - introductory, experimental, and final. The initial assessment of students’ professional knowledge was carried out at the introductory stage. The goal of the experimental stage was to introduce visualization of learning and memorization, mainly, the use of mind maps and charts in students’ professional training. Tasks were developed and used, providing for the creation of mini projects, construction layouts with charts, mental maps (reflecting the professional role of a specialist in construction and architecture fields), features and stages of design, priorities of architectural and construction activities. At the final stage, the final assessment of students’ progress in vocational training and a comparative analysis of the data were carried out, conclusions were drawn about the advisability of visualizing the processes of learning and memorizing in higher education. Teachers’ attitude towards the active implementation of visualization of learning and memorizing was also studied at the introductory and final stages. To determine teachers’ attitude towards the active implementation of visualization of learning and memorizing, the survey was conducted. The introduction of the above-mentioned tasks gave the following results in the experimental group. Namely, there were high growth rates of students with a high level of knowledge (11.5%), 16.4% - with a sufficient level of knowledge and 13.7% - with an average level of knowledge; there was also a decrease in the number of students with low grades (by 16.6%) compared to the control group at the final stage. The number of teachers with positive-promising and positive attitude towards visualization of learning and memorizing increased by 14.3%, the number of respondents with positive-neutral attitude decreased by the same percentage, and there was not a single teacher who retained a negative attitude. The practical value of the results lies in the possibility of using the questionnaire and tasks developed in the real educational process of modern higher education institutions.